AUTHORSHIP AND ARTEFACTS: REMAKING IP LAW FOR FUTURE OBJECTS. - Koepsell, David (Monist, 2010)
An essay on the remaking of intellectual property law on future authorship and artefacts is presented. It offers perspectives on the development of the legal-institutional notion of IP such as letters patent, piracy as privateers, and monopoly copyrights. The author believes that technological innovations have changed the copyright system through arrangements and schemes that treat transactions as exchanges of the right to use and to access a type of intermediary tokens.